Integrated clinical and metabolomic analysis identifies molecular signatures, biomarkers, and therapeutic targets in primary angle closure glaucoma - Kannan, Vishnu; Srimadh Bhagavatham, Sai Krishna; Dandamudi, Rajesh Babu; Kunchala, Haripriya; Challa, Sivateja; Almansour, Abdulrahman I.; Pargaonkar, Ashish; Pulukool, Sujith Kumar; Sharma, Anuj; Sivaramakrishnan, Venketesh (Frontiers in Molecular Biosciences, 2024)
Background Glaucoma is the leading cause of permanent blindness. Primary angle closure glaucoma (PACG) is diagnosed only after the onset of symptoms and can result in irreversible blindness despite the standard intraocular pressure (IOP) reduction therapy. The identification of potential biomarkers associated with prognosis will help improve disease management. This study aimed to identify mechanisms associated with disease progression, potential biomarkers, and therapeutic targets of PACG. Methods The clinical data assessment of IOP, cup/disc ratio (CDR), Retinal Nerve Fiber Layer (RNFL) thickness of control, and PACG group were collected and analyzed for significant differences. The ATP levels were estimated, and targeted metabolomic analysis was performed on aqueous humor and cytokines in plasma. The pathways obtained from the metabolomics data set were compared with those obtained for data sets from the literature. Clinical parameters were correlated with cytokine levels. Targeted metabolomic analysis of cell culture supernatant from TNFα-treated N9 microglia was carried out, and overlap analysis was performed with data obtained from PACG patients. Results Elevated IOP, CDR, ATP, cytokines, and reduced RNFL thickness were found in PACG compared to controls. Analysis of PACG and TNFα-treated N9 microglial cell culture supernatant shows activation of immuno-metabolites. The metabolic pathways of PACG, TNFα, and ATP-treated microglia from the literature show considerable overlap. Biomarker analysis identified clinical parameters, ATP, cytokines, and immuno-metabolites. Conclusion This study shows an association between elevated levels of ATP, cytokines, immuno-metabolism, and potential microglial inflammation with disease progression, rendering these levels potential biomarkers. P2 receptors, cytokines, and IDO1/2 could be potential therapeutic targets.